Prevalence and Determinants of Anemia in Pregnancy, Sana’a, Yemen - Yousef M. Alflah; Iman H. Wahdan; Ali A. Hasab; Dalia I. Tayel (Intelektual Pustaka Media Utama, 2017)
Anemia is a global public health problem in both developing and developed countries, especially among pregnant women. The aim of the study was to estimate the prevalence of anemia among pregnant women in Sana'a governorate, Yemen, and to identify the determinants contributing to it, and to assess knowledge regarding it. The study was conducted using a cross-sectional approach. It included 360 pregnant women attending the maternity clinics of maternity hospitals. A predesigned structured interviewing questionnaire was used to collect data from the pregnant women. Laboratory investigations were done. The prevalence of anemia was found to be 40.3%, and was higher among females aged 35 to less than 45 years, those with poor income and poor nutritional level. The risk of anemia increased with the gestational age, gravidity, decreased birth spacing, drinking tea and coffee after meals, decreased intake of proteins and low level of knowledge and income. The binary logistic regression model indicated a significant impact of the education and occupation on the level of knowledge of pregnant women. Anemia was found out to be a severe public health problem among pregnant women in Yemen. Identified risk factors should be considered for its prevention and control.